Effect of Different Concentrations of Chitosan Biostimulant on Biochemical and Morphophysiological Traits of Stevia Plant (Stevia rebaudiana Bertoni) - M Mehregan (Journal of Medicinal Plants, 2017)
Introduction: Chitosan is one of the polysaccharides containing nitrogen which is synthesized naturally by deacetylation reaction of chitin and is confirmed as one of the efficient biostimulants for improvement of secondary metabolites production in medicinal plants.